Research Trends on Writing Skill in Arabic Language; A Bibliometric Analysis - Safrudin, Ramadhan; Sanah, Siti; Siregar, Sri Dewi Priwarti (Study Program of Arabic Language Teaching, 2024)
This study examines the trends in research on Arabic writing skills from 2011 to 2024 using a bibliometric approach. Data from 32 Scopus-indexed publications were analyzed to identify citation trends, geographical distribution, journal rankings, and research focuses. Data collection techniques included comprehensive searches in bibliographic databases, and data analysis was conducted using bibliometric methods such as citation analysis and co-authorship network analysis. The results show a significant increase in related publications, highlighting the importance of communicative approaches and international collaboration in enhancing writing skills. Specifically, the highest number of cited publications (NCP) occurred in 2020, with an NCP of 6. The highest number of citations from 2011 to 2024 was recorded in 2020, reaching 28. Additionally, 2020 had the highest number of publications, totaling 7, indicating a significant impact of research during that year. Saudi Arabia is the most significant country in research related to writing skills in Arabic. Furthermore, the study categorizes research focuses into three main clusters: students, e-learning, and supporting technologies for Arabic language learning. These insights provide a valuable framework for educators and researchers, guiding future research directions and developing more effective and inclusive teaching methodologies that cater to diverse learning needs. The study concludes that fostering international collaboration and leveraging advanced technologies are essential for the continued enhancement of Arabic writing skills education, ensuring that learners are well-equipped to meet contemporary challenges and advancing the field in a meaningful way.